Developments in Corrosion Protection 2014
DOI: 10.5772/57322
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion of Biomaterials Used in Dental Reconstruction Dentistry

Abstract: although biologically inert, it has poor mechanical properties, on the other hand, steels, which have excellent mechanical properties do not show a good corrosion resistance). Titanium is a material reactive in water, air, or any other electrolyte where it covers spontaneously with a titanium oxide layer. It is considered an inert material, as in contact with the tissue, it is rapidly inactivated forming on its surface a thin, hard, and protective layer of oxide, in less than one second [9, 10, 11, 47]. The ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Here it can be also observed that the depth of the wear scar in the lubricated conditions is greater, however, the micrograph does not appear to show significant damage, only showing fractures and the presence of debris. This phenomenon is due to the fact that in the composite material it presented a chemical reaction known as corrosion, which in dental composite materials causes a swelling in the material, due to the separation of the polymeric chains due to the absorption of a solvent [27], which makes the material softer. Due to the corrosion suffered by the composite material, the attrition-corrosion phenomenon was generated, which caused greater wear in the lubricated condition.…”
Section: Discussionmentioning
confidence: 99%
“…Here it can be also observed that the depth of the wear scar in the lubricated conditions is greater, however, the micrograph does not appear to show significant damage, only showing fractures and the presence of debris. This phenomenon is due to the fact that in the composite material it presented a chemical reaction known as corrosion, which in dental composite materials causes a swelling in the material, due to the separation of the polymeric chains due to the absorption of a solvent [27], which makes the material softer. Due to the corrosion suffered by the composite material, the attrition-corrosion phenomenon was generated, which caused greater wear in the lubricated condition.…”
Section: Discussionmentioning
confidence: 99%